Estimating Elasticities for the Residential Demand of Electricity in Brazil Using Cointegration Models - de Souza, Daniel Morais; Mattos, Rogerio Silva de; Zanini, Alexandre (International Journal of Energy Economics and Policy, 2022)
Estimates of demand elasticities are crucial for the development of a range of energy policy studies, especially in countries of continental dimensions like Brazil. The paper explores the class of cointegration models as a provider of competing methods to estimate income, electricity price, and equipment price elasticities for the residential demand of electricity in Brazil from 1974 to 2016. We compare two cointegration methods: the well-known Johasen’s (1988) approach and the autoregressive distributed lag model of Pesaran et al. (2001). The use of the latter is novel in the electricity demand literature regarding Brazilian studies. The results show that the two models produce similar elasticities and indicate that the residential demand is stable. The long-run elasticities are much larger than the short-run elasticities. In the long run, we find that income is the main determinant of demand, while variations in electricity price and electric equipment price show modest effect on demand.